(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Kseniya A. Kulko (St. Petersburg, Russian Federation) The triad: Orthodoxy, autocracy, people form the basis of the conservative views of F.M.Dostoevsky and A.I. Solzhenitsyn. Based on common worldview constants, thinkers build concepts of a national-conservative persuasion. Their creative heritage is broader than “soil culture”, nevertheless, the ideas of this direction are developing in their journalism. The article presents a comparative analysis of the views of the authors concerning their views on the land, the Russian people and the intelligentsia. An analysis of the texts of Dostoevsky’s “Diary of a Writer”, Solzhenitsyn’s artistic and publicistic miniatures “Krohotki” and his other publicistic works allows us to understand why many of the “soil” issues raised in the 19th century were actualized a century later. The continuity of ideas of authors of different centuries in the context of social and political transformations in society is considered. A significant time period separating Dostoevsky and Solzhenitsyn makes it possible to see not only coincidences and consonances in their work, but also divergences. Key words: F. M. Dostoevsky, A. I. Solzhenitsyn, nativism, land, people, intelligentsia. DOI 10.18522/1995-0640-2021-2-241-253